THE CORRELATION OF SINGLE NUCLEOTIDE POLYMORPHISM IN OXYTOCIN AND OXYTOCIN RECEPTOR GENES AND THE SERUM OXYTOCIN LEVEL IN THE IRAQI MALE CHILDREN WITH AUTISM - HAIDAR A. ABDULAMIR, MSC, PHD,; SALWA J. ABDULLAH AL-AWADI, MSC, PHD,; OMAR F. ABDUL-RASHEED, MSC, PHD, (International Journal of Pharma and Bio Sciences, 2016)
The aim of the present study was to test the possible correlation between oxytocin (rs2770378) and oxytocin receptor (rs53576) polymorphisms with the level of oxytocin in association with the severity of social and cognitive dysfunctions in children with autism. The study was done on 60 males with autism who were recruited from the Pediatric Department at Al-Sader General hospital, Baghdad-Iraq between November 2014 and April 2015. The levels of oxytocin (OXT) were measured in the sera of 60 Iraqi autistic male patients, categorized as mild, moderate and severe (20 patients each) and compared with 26 age- and gender-matched control subjects. The genetic polymorphism OXT/rs2770378 and OXTR/rs53576 was detected by polymerase chain reaction Restriction fragment length polymorphism (PCR-RFLP) method. From the genetic work it was concluded that OXT/rs2770378 polymorphism showed to have an effect on the level of oxytocin in the autistic children that in turn may involve in the pathogenesis of autism. Whereas, OXTR/rs53576 polymorphism showed a non-significant association with autism in the studied children and no effect of this polymorphism was demonstrated on the level of oxytocin.